Sertifikasi Halal sebagai Strategi Peningkatan Kepercayaan Konsumen dan Profesionalitas Usaha: Studi Kasus Donat Qmeuli Tasikmalaya - Shofura Auliya; Muhamad Fajri Muharam; Irdan Nurdiansyah; Araya Ghifary Alba Wahyudi (UIN Sunan Gunung Djati Bandung, 2026)
This qualitative case study analyzes the implementation of halal certification at Donat Qmeuli, a microenterprise in Tasikmalaya City, and its impact on consumer trust. Data were collected through in-depth interview with the owner and direct observation of the production process on November 12, 2025. The findings show that halal certification was systematically implemented with P3H assistance, verification of certified raw materials, and hygienic practices reflecting the halalan thayyiban principle, despite the absence of comprehensive written SOPs. Although certification did not directly boost sales, it significantly enhanced consumer confidence, strengthened the business’s professional image, and facilitated partnerships with modern retailers requiring halal legality. The study emphasizes the need for continuous halal literacy programs and administrative support for SMEs. Limited to a single case, future research should expand to multiple bakery SMEs for a more comprehensive mapping of halal implementation.